PERILAKU PETANI DALAM PENGENDALIAN HAMA TERPADU PADA BUDIDAYA PADI DI KECAMATAN CIKEDUNG - Lukman Effendy; Muhamad Tassim Billah; Doni Darmawan (Jurnal Inovasi Penelitian, 2020)
Pest control is one of the methods used to treat and control pest attacks. To change the behavior of farmers can be transformed which leads to the knowledge, attitude and skill of farmers about PHT in the cultivation of rice. So the writer would raise the title of the farmer's behavior in the unified pest control (UPC) of raising rice (Oryza sativa) in the district district district district district district." Dani's goal to describe the behavior of farmers in integrated pest control in rice raising, analyzing the impact of farmers' behaviour in integrated pest control in rice production and formulating a strategy to improve the behavior of farmers in rice production in the United States and developing a plan to increase the behavior of farmers in the rice creation from March 9, 2020, to June 30, 2020, in the village of jambak district district. The data-collection technique USES observation, diffusion and charge of questionnaires by the number of respondents to 100 farmers. Studies have found that the behavior of farmers toward common pest in bulware-based rice yields is in the current category from linear regression analysis, it has been shown that there is an influence between the variables of the characteristics of the 0,003, the variables of the UPC 0,000 principle and the elective factor. Kendall's w analysis shows a low value of 7.99 on the UPC principle variable, the indicator of farmers to UPC expert.